Between Collaboration and Resistance: Papers from the 21st Workshop on the History and Memory of National Socialist Camps and Extermination Sites - Georg, Karoline; Meier, Verena; Oppermann, Paula A. (Metropol Verlag, 2020)
The articles in this volume reflect on resistance towards and collaboration within NS camps and extermination sites. Exploring cases from various European countries, they illuminate the range of behaviours between those reference points and explore its perception both after the war and today.